Neurosurgery training in Nepal: then and now - Chaurasia, Bipin; Raut, Rupesh; Chaurasia, Raushan; Thapa, Amit (Frontiers in Surgery, 2023)
Introduction: Training of neurosurgery in world is not uniform. Difference in training period is one of the major problem for world neurosurgery not united as “one neurosurgery”. Material and Methods: We tried to evaluate the conditions of current Neurosurgery training in Nepal by exploring all the different institutions providing the training. Results: Due to various challenges neurosurgery training in Nepal is different in different institutes. Many got trained from abroad due to lack of training seats. Discussion and conclusions: The future of neurosurgery training in Nepal is bright. With continued investment in education and training, and the adoption of new technologies and techniques, it is likely that neurosurgery will continue to thrive and make a positive impact on the health and well-being of the Nepali population.